Analysis of Factors Affecting Brand Loyalty: A Case Study of Janji Jiwa Coffee - Danu Triwinarko Widodo; Hapsari Setyowardhani (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2019)
As the Indonesia World Records Museum (MURI)’s 2019 winner of the category of fastest growing coffee shop in 2019, Janji Jiwa strives to maintain and increase its number of customers. This study replicates Kim and Lee's (2016) research on how coffee shops in South Korea increase their brand loyalty. It employs the purposive sampling method with 206 respondents and analysis is conducted using Structural Equation Modeling (SEM). The findings of the study reveal that customer brand identification has a positive effect on brand involvement, but no positive effect on brand-decision involvement. Both self-congruity and service value have a positive effect on brand involvement and brand-decision involvement. In addition, brand involvement and brand-decision involvement have a positive effect on brand satisfaction and brand loyalty. Finally, brand satisfaction has a positive effect on brand loyalty. Managerial implications and recommendations related to these findings will be discussed further in order to guide future research.